Influence of Structural System on Behavior of Reinforced Concrete High-rise Buildings Subjected to Lateral Loads - A. Kewalramani, Manish; Ahmed Mohamed, Osama (International Journal of Psychosocial Rehabilitation, 2020)
The construction of high-rise reinforced concrete buildings is high in demand worldwide inviting new challenges in terms of structural analysis and design. Lateral loads resulting from wind or earthquake in any high-rise building are usually resisted by a system of coupled shear walls. However, in case of very tall buildings with reduced stiffness sufficient lateral stiffness needs to be provided by carefully examining feasible structural systems. The present work presents a comparative analysis aimed towards selection of optimal structural system by measuring structural efficiency in terms of parameters such as time-period, storey displacement, drift, lateral displacement, base shear and core moments. The results obtained are compared among various structural systems to determine a suitable structural system that can be used for high-rise concrete buildings. The study is based on incorporating different structural systems on the same building so as to have a comprehensive comparison based on identical conditions. The results are determined using a commercial structural analysis and design software – ETABS. The main emphasis is to study behavior of these structural building models subjected to wind load in both X and Y directions.